The Analysis of the Transformation of Forest Landscapes in the Eastern Zangezur Region of Azerbaijan Based on Satellite Imagery - Abdurahmanov, Faig (Human Geography Journal, 2023)
Forested areas, which are considered as the most valuable national natural assets of Azerbaijan, encompass the interconnectedness of soil, water, trees, shrubs, herbaceous plants, wildlife, and microorganisms in their biological development. For this reason, the protection and research of the forests are considered one of the important studies. In this article, we have studied the forests of the Eastern Zangezur region where formed based on the decree of the President of the Republic of Azerbaijan, Ilham Aliyev, on July 7, 2021, which united the districts of Kalbajar, Lachin, Gubadli, Zengilan, and Jabrayil. The Eastern Zangezur region has a rich forest area which approximately a quarter of the region is covered with forests.  However, unfortunately, the forest areas within the district have been strongly degraded and destroyed over the past 30 occupation years. The main causes of this destruction are attributed to illegal logging, deliberate forest fires, wars and other factors.The information obtained from various official sources (written articles, statistics of the Ministry of Ecology and Natural Resources, various maps etc.) shows that the forests of our study area were substantially degraded during the occupation period.In the article, the forest areas in the Eastern Zangezur region have been thoroughly investigated, and the transformation of forests over the years has been assessed based on the analysis of satellite imagery. For study, we have used images get from LANDSAT and AzerSky satellites. The level of degradation of the forest area in the region was calculated with the help of GIS and Mathematical methods. As a result of this assessment, maps and diagrams have been prepared.This information will play a major role in the evaluation of the forest area of the Eastern Zangezur region, the proper conduct of forest restoration and construction works, as well as the placement of agriculture. It will also show the environmental damages caused by wars.